Animal Models of Pain - Ma, Chao.; Ma, Chao.; Zhang, Jun-Ming.; Zhang, Jun-Ming. (Neuromethods,, 2011)
With the loss of work days, the price of health care and payments for compensation, litigation, and malpractice, and the overwhelming cost of human suffering, chronic pain syndromes affect humanity enormously on both an economic and personal level. In Animal Models of Pain, expert investigators in the field provide a consolidated review of the current state of pain research by capturing the diversity of animal models that are used to investigate pain mechanisms, which range from surgical incision to mechanical compression and from spinal cord injury to cutaneous/local inflammation and beyond. As a volume in the respected Neuromethods series, this book delivers its vital content through detailed descriptions of a wide variety of step-by-step laboratory methods. Authoritative and cutting-edge, Animal Models of Pain seeks to lead scientists closer to the ultimate goal of improving the quality of life and relieving the unbearable burden of chronic pain for millions of people throughout the world.